Epidermal growth factor receptor targeting and challenges in glioblastoma - Thorne, Amy Haseley (Neuro Oncol, 2016)
With the evolution of technology, there is now a deeper understanding of glioblastoma as an inter- and intraheterogeneous disease comprising a multitude of genetically and epigenetically different cancer cells. Greater characterization of glioblastoma at the molecular level has improved its initial pathophysiological staging and classification. With this knowledge comes the hope that more efficacious therapies to combat this highly lethal disease are on the horizon. One possibility for intervention is represented by the targeting of epidermal growth factor receptor (EGFR), which is amplified and mutated in a large subset of patients. In this review, we provide a brief overview of EGFR and its mutated form, EGFR variant III, describing the downstream cellular pathways activated by each receptor, available animal models, therapeutic strategies to inhibit the receptor, and possible intervention routes to efficiently target this receptor and prevent the emergence of resistant mechanisms which to date have hampered a successful therapeutic outcome.